2020
DOI: 10.3390/ijerph17010312
|View full text |Cite
|
Sign up to set email alerts
|

A Qualitative Analysis of an Aerobic Interval Training Programme for Obese Outpatients Carried Out in a Hospital Context

Abstract: Purpose: To describe the experience of obese adults following participation in an indoor aerobic interval training (AIT) intervention. Methodology: Qualitative, in-depth semi-structured individual interviews, using phenomenology, with 24 obese adults (body mass index (BMI) ≥30 kg/m2) from the Endocrinology Department, at the Severo Ochoa Hospital in Leganés (Madrid). Questions were related to: (a) The physical activity (PA) programme, (b) their perspectives of the activity and exercise environment and (c) the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 40 publications
(42 reference statements)
0
2
1
Order By: Relevance
“…This finding is in line with previous studies, that finding ways to resolve issues at hand and seeking help from others have been shown to be adaptive coping strategies for Chinese people, and linked to lower psychological maladjustment. By contrast, self-blame, fantasizing and avoidance were related to maladaptive coping strategies, and linked with more negative outcomes [19,20]. However, we did not find the support for the prediction of any coping strategies on trajectory of change over time for psychological well-being and mental health risks.…”
Section: Discussioncontrasting
confidence: 84%
See 1 more Smart Citation
“…This finding is in line with previous studies, that finding ways to resolve issues at hand and seeking help from others have been shown to be adaptive coping strategies for Chinese people, and linked to lower psychological maladjustment. By contrast, self-blame, fantasizing and avoidance were related to maladaptive coping strategies, and linked with more negative outcomes [19,20]. However, we did not find the support for the prediction of any coping strategies on trajectory of change over time for psychological well-being and mental health risks.…”
Section: Discussioncontrasting
confidence: 84%
“…Previous research looking at the link between the six coping strategies assessed in this research showed that coping with stress through problem solving and seeking help were linked to lower depressive symptoms for first-year university students [19,20], and correlated with post-traumatic growth among survivors of traumatic events [21,22]. On the other hand, other coping strategies like self-blame, avoidance, fantasizing or rationalization correlated with greater depressive symptoms [19,20]. While self-blame and avoidance have been shown to be associated with greater post-traumatic growth [21], results in relation to the perception of post-traumatic growth should be interpreted with caution.…”
Section: Depressive Symptomsmentioning
confidence: 78%
“…Exercise adherence in general seem to be largely dependent on motivation and this is also the case with obese individuals. Cabanillas-Cruz et al [10] conducted a study with obese individuals that underwent an exercise program in a hospital, describing that the main sources of motivation were weight loss and health improvement, while enjoyment during exercise was found to help patients' engagement in the program.…”
Section: Exercise In Obesity and Ageingmentioning
confidence: 99%